Respuesta :

Answer: [tex](f\°g)(-2)=-5[/tex]

Step-by-step explanation:

 The first step is substitute the function [tex]g(x)=\sqrt{(x+3)}[/tex] into the function [tex]f(x)=-7x+2[/tex]

[tex](f\°g)(x)=-7(\sqrt{(x+3)})+2\\(f\°g)(x)=-7\sqrt{(x+3)}+2[/tex]

Now, you need to substitute x=-2 into [tex](f\°g)(x)=-7\sqrt{(x+3)}+2[/tex] and simplify the function.

Finally you get that [tex](f\°g)(-2)[/tex] is:

[tex](f\°g)(-2)=-7\sqrt{(-2+3)}+2\\(f\°g)(-2)=-7\sqrt{1}+2\\(f\°g)(-2)=-7(1)+2\\(f\°g)(-2)=-7+2\\(f\°g)(-2)=-5[/tex]

Answer:

-5

Step-by-step explanation:

I just took it and got it right.